An assessment of presumptive tax in Uganda: Evaluating the 2020 reform and four alternative reform scenarios using UGAMOD, a tax-benefit microsimulation model for Uganda - Waiswa, Ronald; Lastunen, Jesse; Ayo, Joseph Okello; Nalukwago, Milly; Barugahara, Tina; Rattenhuber, Pia (WIDER Working Paper., 2021)
Presumptive tax, a final tax on business income, was introduced in Uganda in 1997. The latest reform to the regime in July 2020 sought to make the system more progressive, simpler and fairer to small firms. In this work, we evaluate the reform, focusing on its revenue implications based on simulations using UGAMOD, a tax-benefit microsimulation model for Uganda. Our findings suggest that, assuming full compliance, the reform reduces tax revenue potential by between 48-72 per cent from the previous rules. Interviews with staff at the Uganda Revenue Authority point to further challenges with the new rules, including slow implementation, ineffective enforcement and enduring complexity. To address these concerns, we modelled a number of hypothetical reform scenarios, including a 1 per cent and 1.5 per cent flat tax regimes for small businesses with turnover between UGX10-150 million. A low flat tax rate would be a major improvement to the existing presumptive tax regime, as it satisfies the calls for further simplification, is estimated to generate more short-term revenue than the current regime based on the modelling, and has realistic potential to attract more presumptive taxpayers over time.